Analysis and construction for threshold signature scheme based on game theory - ANGJie W; AIYong-quan C; IANYou-liang T (Tongxin xuebao)
The concept of “rational player” is introduced to make threshold signature system more general.In this new primitive,all players are regarded as rational individuals in the sense that they always try to maximize their profits as the goal at any phases.Each player's strategy and utility in key generation and signature synthesis phases are analyzed based on game theory.It is proved that rational players have no motivation to participate in signature in traditional threshold signature scheme,which might cause it impossible to complete threshold signature.Finally,the mechanism of rational key distribution and rational signature synthesis is proposed.Analysis shows the new method is more applicable than the previous schemes in the real-world applications.